PENENTUAN AKTIVITAS ISOLAT ANDROGRAFOLID TERHADAP α-AMILASE DAN α-GLUKOSIDASE MENGGUNAKAN METODE APOSTOLIDIS DAN MAYUR - Ichwan Ridwan Rais; Agung Giri Samudra; Sitarina Widyarini; Agung Endro Nugroho (Majalah Obat Tradisional, 2013)
Disorders of carbohydrate metabolism can lead to diabetes mellitus. Carbohydrates  are metabolized in the gastrointestinal tract  into simple glucose and absorbed into the bloodstream and affected blood glucose levels. The absorption process is catalyzed by α- 1 ,4 - glycoside breaking bond  enzyme , namely α - amylase and α -1 ,6 - glycoside breaking bond  enzyme, namely α – glucosidase. They are found in the intestinal cells. Research had been conducted in an effort to develop an alternative treatment of diabetes mellitus by testing the ability of isolates of andrographolide in inhibiting α-amylase activity and α-glucosidase in vitro. Andrographolide isolates showed fairly good activity in inhibiting α-amylase ( IC50 = 1,.49 mg/mL) and weak in inhibiting α-glucosidase (IC50 = 38,86 mg/mL). Inhibition of α-amylase activity is evidence of one mechanism of andrographolide in reducing carbohydrate metabolism that can affect blood glucose levels and indicates that andrographolide is  a potential alternative medicine in addressing diabetes mellitus .